Effect of climate variability on Collaria scenica (Hemiptera: Miridae) on the Bogotá plateau - Rodríguez Roa, Andrea; Arce Barboza, Blanca; Boshell Villamarin, Francisco; Barreto Triana, Nancy (Universidad Nacional de Colombia, 2021)
The aim of this research was to study the effect of climatic conditions on the population of the grass bug Collaria scenica (Stal, 1859) using agroclimatic models and analyzing its behavior under interannual variability scenarios related to El Niño-Southern Oscillation (ENSO) events. The population fluctuations of this grass bug were modeled, estimating significant climatic variables in the presence of nymphs and adults with a multiple linear regression analysis. The population distribution of this insect in relation to the occurrence of the El Niño and La Niña phenomena on the Bogota plateau was analyzed based on variations of the sea surface temperature (SST) in the tropical Pacific and their impact on climate variables. The maximum and minimum temperatures, precipitation and evapotranspiration showed higher significance for this pest than the other variables. The optimal growth and development conditions for this grass bug occurred during periods with a higher daily thermal amplitude and high precipitation values, which highlights the positive effect of abundant, but not excessive, rain. This study helped to determine the population growth during the two seasons of the year with higher rainfall in the area, which correspond to March-May (MAM) and September-November (SON), mainly in the following season after the dry quarter of December-February (DJF). Important increases occur in the El Niño event because of the greater accumulation of heat units during this phenomenon based on increases in air temperature that favor insect growth.